THE ROLE OF LEGAL PHILOSOPHYIN BUILDING THE MORAL OF THE NATION'S CHILDREN - Tri Madya Wianto; Yusuf Setyadi (INTELIGENSIA MEDIA, 2022)
Philosophy of law in the science of law is the culmination of the legal structure itself, in making legal instruments, these instruments must protect the entire Indonesian nation with the aim of underlying the moral development of the nation's children, because of the importance of morality in the life of society, nation and state in an effort to establish unity and unity. Indonesian nation. Therefore, legal philosophy expressly provides fundamental views on law, with the aim of building the morale of the nation's children so that in the future they become ethical, moral office holders and uphold the law in its implementation. In this writing, the writer uses the Theory of Justice and Human Law.